LEARNING PARADIGM OF PANCASILA STUDENT PROFILE ON ISLAMIC RELIGIOUS EDUCATION IN GRADE 1 SDN PACING - Desi Asmarita (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
Government policy related to efforts to create a generation of nations that practice the values of Pancasila through the learning process of the Pancasila student profile paradigm. PAI learning as one of the subjects taught in schools should carry out a learning process based on the Pancasila student profile. In reality, in the process of instilling Pancasila values, educators still experience various difficulties in their application. This study used descriptive qualitative method with data collection through interviews, observation and documentation. Test the validity of the data using triangulation techniques. Data analysis techniques are carried out by reducing data, data supply and verification to be concluded. The results showed that SDN Pacing has implemented the learning paradigm of the Pancasila student profile. PAI learning also carries out learning in accordance with the profile of Pancasila students, namely faith and piety, independence, creativity, global celebrity, critical reasoning, and mutual assistance. Its application in PAI learning starts from the introduction to the closing activities which contain the instillation of values based on the Pancasila student profile.